2018
DOI: 10.1177/1479164118782091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the lamina cribrosa in patients with diabetes mellitus using enhanced depth imaging spectral-domain optical coherence tomography

Abstract: The results of this study showed that the optical coherence tomography measurement of lamina cribrosa revealed thicker and more anteriorly positioned lamina cribrosa for patients with diabetes mellitus compared with those for healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…In the current study, some patients had a comparable to or even smaller LCCI in NTG than in contralateral healthy eyes, suggesting that non-IOPrelated factors such as ONH blood supply may play a more significant role in glaucoma development in these eyes. Akkaya et al 54 have reported that diabetic patients had thicker and more anteriorly positioned LC compared to healthy controls. Of the 76 patients included in the present study, nine (11.8%) had diabetes mellitus (DM).…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, some patients had a comparable to or even smaller LCCI in NTG than in contralateral healthy eyes, suggesting that non-IOPrelated factors such as ONH blood supply may play a more significant role in glaucoma development in these eyes. Akkaya et al 54 have reported that diabetic patients had thicker and more anteriorly positioned LC compared to healthy controls. Of the 76 patients included in the present study, nine (11.8%) had diabetes mellitus (DM).…”
Section: Discussionmentioning
confidence: 98%
“…These changes have been linked to ischemia as well as the neuroprotective effects of diabetes. [12][13][14][15][16][17] Even in glaucomatous eyes the effect the ONH is different between those with and without DM. 18 OCTA can demonstrate ischemia of the ONH and LC, which can lead to ganglion cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and histological changes in the lamina cribrosa are investigated in ocular diseases and in some systemic diseases with ocular involvement (15)(16)(17)(18)(19)(20)(21)(22). Particularly, based on the consideration that it plays a role in the pathogenesis in patients with glaucoma, changes in the lamina cribrosa are investigated (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…LCT was lower in patients with retinal vein occlusion as compared with healthy individuals (21). In a study evaluating the lamina cribrosa using OCT, a thicker and more anteriorly positioned lamina cribrosa was demonstrated in patients with diabetes mellitus as compared with healthy controls (22). A study conducted in healthy adults (≥18 years old) reported a positive correlation between LCT and age (23).…”
Section: Discussionmentioning
confidence: 99%